Multifrequency approximation and average modelling of an isolated bidirectional dc–dc converter for dc microgrids. Issue 6 (1st May 2016) - Huang, Jun; Wang, Yue; Li, Zhuoqiang; Lei, Wanjun
Abstract : This study presents a generalised analysis of isolated bidirectional dual active bridge (DAB) dc–dc converter with triple‐phase‐shift (TPS) control. The multifrequency approximation is used to analyse performance characteristics of DAB, and a novel numerical solver is developed to determine the optimised modulation scheme based on TPS control. Specially, the proposed solver can be considered as a unified solver for determining the optimised operation of DAB with required transmission power and voltage conversion ratio. The multifrequency average model of DAB is then described in this study. A universal control‐to‐output‐voltage transfer function is derived for DAB with any modulation scheme, and the closed‐loop operation is discussed based on the proposed average model. Finally, a laboratory prototype is implemented and experimental results verify the theoretical analysis.